2016
DOI: 10.1080/03075079.2016.1147721
|View full text |Cite
|
Sign up to set email alerts
|

New public management and research productivity – a precarious state of affairs of academic work in the Netherlands

Abstract: New Public Management reforms have fostered universities to focus on performance and competition which has resulted in different pressures to perform and disruption of strong teaching-research balance at universities. The imbalanced division of teaching research workloads may be gendered and can strengthen the differences in research productivity among male and female academics. This study uses survey data of Dutch academics carried out in 2015 at selected three universities to understand how pressure to perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 48 publications
4
54
0
8
Order By: Relevance
“…Moreover, these studies do not account for the changes to the academic profession and work in recent decades, which have been strongly influenced by research assessments, institutional pressures towards performativity, 'publish or perish' dynamics and demands that research impact is evidenced (Chubb & Watermeyer, 2017;Kenny, 2018;Martin-Sardesai, Irvine, Tooley, & Guthrie, 2017). These changes to the current working environment in academia are bound to influence academics' behaviours and strategies concerning their research agendas (e.g., Brew & Lucas, 2009;Horta & Santos, 2019;Leisyte, 2016). Considering this context, the present study sought to assess how psychological traits are associated with academics' research agendas.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these studies do not account for the changes to the academic profession and work in recent decades, which have been strongly influenced by research assessments, institutional pressures towards performativity, 'publish or perish' dynamics and demands that research impact is evidenced (Chubb & Watermeyer, 2017;Kenny, 2018;Martin-Sardesai, Irvine, Tooley, & Guthrie, 2017). These changes to the current working environment in academia are bound to influence academics' behaviours and strategies concerning their research agendas (e.g., Brew & Lucas, 2009;Horta & Santos, 2019;Leisyte, 2016). Considering this context, the present study sought to assess how psychological traits are associated with academics' research agendas.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of excellent researchers against the infusion of peers with a similar profile that can be gleaned from our analysis brings to the fore a caveat, however: top performers do not benefit from the potential access to other excellent researchers, as the number of their A-rated publications slightly diminishes. This might be due to several reasons: in a context populated by excellent researchers, competition for scant resources, such as internal funding, is bound to get harder, alongside minor opportunities for differentiation in terms of time devoted to research as against teaching (Krücken 2014;Leišytė 2016). Another reason could be linked to the effort of transferring knowledge to less expert colleagues: that demanding activity may lessen attention towards one's own research.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, past productivity has been considered an important estimator of future research excellence (Williamson and Cable 2003). Since the number of past publications tends to overlook the quality of work as an important dimension of research excellence, most university systems target the number of papers published in prestigious journals (Groot and García-Valderrama 2006;Horta, Dautel, and Veloso 2012;Leišytė 2016). Given the relevance of both quantity and quality of past performance in explaining variation in research excellence, we propose that:…”
Section: Individual Qualitymentioning
confidence: 99%
“…Our study, based on 100 interviews at faculties of social sciences and economics in the Netherlands, Sweden and the United Kingdom, revealed that performance management and measurement can be perceived as part of a continuous process that has been increasingly influential in the systems of higher education in all three countries. Performance measurement seems to have persevered in such systems, not so much for the supposed improvement of the quality of the primary process but because of its impact on the academic workforce (Leišytė 2016).…”
Section: Conclusion and Theoretical Reflectionmentioning
confidence: 99%
“…Managerialism has resulted in an ever-increasing number of university rankings that have consequently become increasingly important to European institutions of higher education (Devinney, Dowling, and Perm-Ajchariyawong 2008). Such developments have prioritized self-governmentality, changed funding mechanisms, especially for research, and thus substantially influenced the work of academics (Kehm and Lanzendorf 2006;Scott 2008;Leišytė 2016). Initially, academics met the implementation of managerialist strategies, particularly ones to ensure accountability for quality and transparency in teaching and research (Bryson 2004), with resistance.…”
Section: Introductionmentioning
confidence: 99%